Mindfulness e autocompaixão como fatores protetores contra ansiedade e estresse durante a pandemia do covid-19: uma intervenção breve assíncrona, aleatorizada e controlada realizada via aplicativo móvel - Silva, Leonardo Júnior Souza (2021)
The purpose of this study was to test the effectiveness, and the sustained effect (follow-up) of a four-week mindfulness intervention in reducing anxiety and stress in a group of Brazilian university students, the intervention was adapted to be made available through the application Neurosaúde, created as part of this work to serve as a platform for intervention. The research as a whole took place in a virtual environment, with forty-eight participants recruited who were randomly allocated to the intervention group or to the waiting list control. Measures were used to access the levels of mindfulness, anxiety and stress before, after the intervention and at the 4-week follow-up. Applying the intention-to-treat analysis, we found significant differences between the groups for the measurement of anxiety in the follow-up with a large feat size (F (2, 92) = 10.275, p = 0.000, η2 = 0.183). Our results suggest that the 4-week mindfulness intervention through a mobile application was able to act as a protective factor against the anxiety developed by university students during the occurrence of the pandemic caused by COVID-19, whereas while the treatment group maintained levels reduced anxiety the control group demonstrated a continuous increase in anxiety in the post-test and follow-up that coincided with the first wave of COVID-19 in the region where the participants lived.